Prediction of Gingerol from Red Ginger Plant (Zingiber officinale var. rubrum) for 5-Hydroxytryptamine Release Stimulant as Antirheumatic - Ratno Setyobudi; Fendy Prasetyawan (PT Pustaka Cendekia Publisher, 2025)
Rheumatoid arthritis (RA) is a debilitating autoimmune condition characterized by chronic joint inflammation and pain, often managed with conventional treatments that can present serious side effects. This study investigates the potential of gingerol, the primary bioactive compound found in red ginger (Zingiber officinale var. rubrum), as a natural alternative for RA management. Utilizing in silico methodologies such as molecular docking and dynamics simulations, the research predicts that gingerol acts as a stimulant for the release of 5-hydroxytryptamine (serotonin), a crucial neurotransmitter involved in pain regulation and inflammation modulation. The analysis reveals a high probability (0.960) of gingerol's activity in enhancing serotonin release, suggesting its significant role in mitigating inflammatory responses. The interaction mechanism of gingerol with serotonin receptors indicates a pathway for its therapeutic action, reinforcing its potential as a safe and effective herbal medicine for RA treatment. Further research, including in vitro and in vivo validations, is warranted to explore the efficacy of gingerol as a viable anti-rheumatic agent.